1997
DOI: 10.1016/s0266-7681(97)80066-6
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Results of Ganglion Aspiration by the Use of Hyaluronidase

Abstract: We present the results of a prospective randomized trial comparing the treatment of ganglia by aspiration under local anaesthetic and either instillation of steroid alone or with the prior use of hyaluronidase. Thirty-five patients were treated in each group and followed up for 2 years. The cure rate with the combined use of hyaluronidase and methylprednisolone was 89%, compared to 57% when treated by aspiration and instillation of methylprednisolone alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
5
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 8 publications
2
55
5
1
Order By: Relevance
“…Subsequent trials have demonstrated much less optimistic results. 18,21 In fact, results appear no better than simple aspiration alone, probably based on the fact that neither technique addresses the actual cause of the cyst. A number of techniques have been developed that are actually designed to increase inflammation within the ganglia to enhance scarring and thus close the potential space of the empty cyst and prevent recurrence.…”
Section: 25mentioning
confidence: 99%
“…Subsequent trials have demonstrated much less optimistic results. 18,21 In fact, results appear no better than simple aspiration alone, probably based on the fact that neither technique addresses the actual cause of the cyst. A number of techniques have been developed that are actually designed to increase inflammation within the ganglia to enhance scarring and thus close the potential space of the empty cyst and prevent recurrence.…”
Section: 25mentioning
confidence: 99%
“…Complications of surgery include wound-healing complications, such as infection, neuroma or keloid formation, and the presence of a scar. Other reported complications include scapholunate dissociation, joint stiffness, damage to the terminal branches of the posterior interosseous nerve, and decreased grip strength along with the risks associated with the use of general anaesthesia and upper limb tourniquet (15). We had a complication rate of 8.5%.…”
Section: Discussionmentioning
confidence: 89%
“…Comparison of surgical excision with aspiration and steroid injection showed wide gap in the results [6] , with success rate of around 94% for surgical excision and mere 61% for aspiration and steroid injection. Varley et al in their study found only 33% -57% success rates with either aspiration alone or in combination with steroid injection [8,9] but when combined aspiration with hyaloronidase and triamcinalone injection, the success rate shot upto 89% [8] . Surgical excision and closure of capsule has found to be more successful of all treatment option with success rates of around 92% [2,3] .…”
Section: Discussionmentioning
confidence: 95%